Synthesis of Arylated Benzofurans by RegioselectiveSuzuki–Miyaura Cross‐Coupling Reactions of 2, 3‐Dibromobenzofurans‐ and 2, 3, 5‐Tribromobenzofurans. (26th May 2014) - Hussain, M.; Thai Hung, N.; Abbas, N.; Khera, R. A.; Malik, I.; Patonay, T.; Kelzhanova, N.; Abilov, Z. A.; Villinger, A.; Langer, P.
<x xml:space="preserve">Abstract</x> Arylated benzofurans were prepared by regioselectiveSuzuki–Miyaura cross‐coupling reactions of 2, 3‐dibromobenzofuran. The reactions proceeded with very good site‐selectivity in favor of the more electron deficient position 2. The Suzuki–Miyaura reactions of 2, 3, 5‐tribromobenzofuran also proceeded in favor of position 2.